A pilot study of ankle instability following long segment fibular graft harvesting - Halim, Ahmad Sukari; Wan, Zulmi; Muhamad, Mahayiddin; Ibrahim, Mohd Yusof (2002)
Fibular graft is a useful technique to restore-skeletal integrity of bony defects.Despite the benefits of this procedure,there are reported problems associated with donor site, particularly with regards to ankle stability.A cohort study was performed on patients who had undergone tong segment fibular graft resection of minimum 15 em in length. A total of ten patients ranging from 12 to 64 years old were included in the study.The assessment performed after a minimum of 4 months following the operation.Ten pairs of legs were evaluated with contralateral normal legs as control (a total cf ten legs).The objective assessment of ankle morbidity was done based on Maryland Foot scoring system. Radiological assessments included plain radiograph in syndesmotic views, on both non weight bearing supine position and weight bearing standing position.The axial CT scan slice done at the level of 9 mm above the tibial plafond was assessed to measure the anterior and posterior syndesmotic interval Subjective assessments revealed score ranging from 78 to 99% according to Maryland Foot scoring system.Osteoporosis of distal fibula of the donors side was present in 89%.Despite the significant radiological changes of the residual distal fibula and the ankle, the subjective assessment of the ankle morbidity yielded good or excellent results.The residual distal fibula of 5.5 em or Jess was associated with low score of less than 85%.Leaving a minimum of 7 em length of the residual distal fibula is advisable to minimize symptoms of ankle instability.